Masculinity and Self-Perception: The Emotional Drivers of Male Aesthetics - Pikoos, Toni D.; Buchanan, Ben G. (Facial Plastic Surgery, 2025)
Men comprise up to 16% of aesthetic patients; however, the unique motivations and experiences of male patients remain understudied. We aimed to synthesize evidence on social, emotional, and psychopathological drivers of male interest in aesthetic procedures and outline clinical implications for aesthetic practitioners.Changing expressions of masculinity, media, and technology, as well as social, romantic, and professional influences, were explored. Research regarding psychopathology and body dysmorphic disorder (BDD) in male aesthetic patients was reviewed.Modern, fluid notions of masculinity have normalized aesthetic interventions among male patients. However, men experience ongoing stigma as a barrier to accessing treatment. Men display similar motivations to women, but report professional drivers more frequently. Mental health concerns and BDD prevalence rates are inconsistently reported among male aesthetic patients, but are likely to predispose males to more challenging treatment experiences. Clinical implications and recommendations for working with male patients are discussed.As men continue to undertake cosmetic procedures more frequently, practitioners should take care to adapt their approaches to the unique preferences of male patients. This includes shifts in language, advertising, consultation, and treatment planning to overcome stigma and barriers to access, while prioritizing safe, ethical care.
Keywords: male aesthetics; patient psychology; treatment motivations; body image; self-perception